2017
DOI: 10.1007/s00586-017-5191-7
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging can predict surgical outcomes of patients with cervical compression myelopathy

Abstract: FA in spinal cord DTI can moderately predict surgical outcomes. DTI can serve as a supplementary tool for decision-making to guide surgical intervention in patients with CCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 41 publications
2
30
1
Order By: Relevance
“…Furthermore, multilevel compression was also not predictive of a poorer neurological outcome. While, these results are consistent with some studies found in literature [8,[37][38][39][40], other studies, notably those derived from the AOSpine multicenter studies on DCM, have shown contradictory results [11,41]. Our results may partially be due to our relatively small cohort and may have been underpowered to detect statistically significant differences.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, multilevel compression was also not predictive of a poorer neurological outcome. While, these results are consistent with some studies found in literature [8,[37][38][39][40], other studies, notably those derived from the AOSpine multicenter studies on DCM, have shown contradictory results [11,41]. Our results may partially be due to our relatively small cohort and may have been underpowered to detect statistically significant differences.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the concept that FA can be used in the assessment of the degree of severity of DCM with greater accuracy. [12][13][14]34,43] Our results support what has been previously suggested-higher values of preoperative FA can be considered as a positive prognostic factor of functional recovery [13,34,37]. It was interesting to note that, FA values were not different between best and normal responders at 3-months, and this potentially indicates a 3-month FA MRI may be too early to detect changes.…”
Section: Discussionsupporting
confidence: 87%
“…We included 7 articles studying the correlation between preoperative DTI metrics (FA) and postoperative mJOA scale, reported from 2013 to 2019. Two articles 9,14 claimed a nonsignificant correlation, while the rest 5,[15][16][17][18] claimed a significant correlation. Note, Shabani et al 18 showed a negative correlation between preoperative FA and the postoperative DmJOA (difference between post-and preoperative mJOA), while the other studies showed a positive correlation.…”
mentioning
confidence: 96%
“…Diffusion tensor imaging (DTI) has been demonstrated to have prognostic value for CM . In CM, demyelination is believed to be the main pathological change in the spinal cord, and this demyelination changes the organization of nerve fiber bundles, resulting in changes to DTI‐related signals.…”
Section: Introductionmentioning
confidence: 99%